KATA BENDA DALAM BAHASA INGGRIS DAN BAHASA TETUN (ANALISIS KONTRASTIF) - May, Evangelin De Jesus (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT   This research entitled “Nouns in English and Tetun Language (Contrastive Analysis) is written to fulfill the requirement in finish the study in English Department, Faculty of Humanities Sam Ratulangi University. The aims of this research are to classify and describe kinds of nouns that contain in English and Tetun language. The researches of nouns in English are common nowadays, people can find them easily on grammar book or in internet, while the research of nouns in Tetun language is not common. Therefore, by this research, people can learn more about nouns in Tetun language that is contrasted with English. The theories that used in this research are from Frank (1972) and Lado (1979) concept. In this case, data classification and description, the kind of nouns explained as follows: proper noun, concrete or abstract noun, countable or noncountable noun and collective noun. The result of this research shows that the nouns in English and Tetun language are the same; they have the same kinds of nouns looking from the meaning. But, there is also a difference between these two languages. The difference is at the countable noun. In English, a countable noun show by addition –s in the end of the word to show the plural, while in Tetun language, the countable noun show by number. There are similarities and differences of kinds of nouns between these two languages that found in this research. So that, the writer suggest to all the readers who interest to learn more about Tetun language can read this research or do a research in Tetun language further.   ________________________ Keywords: Nouns, English, Tetun Language